Study Behaviour, Home Environment and Achievement in English - Ismail, Norasiah (1995)
This study was basically an attempt to obtain an insight into the pattern of relationships among students achievement in English, study behaviour variables and home environment variables. Specifically, the study aimed to determine the relationship of each of the study behaviour variables to student achievement in English, the relationship of each of the home environment variables to student achievement in English, the relationships among the study behaviour variables and home environment variables, the combined effect of the various study behaviour variables and home environment variable on student's achievement in English. This study was conducted in fourteen secondary schools in Kuala Lumpur. A total of 485 boys and 515 girls from Form Four Science, Arts and Commerce streams were involved. The independent variables in this study were study behaviour and home environment. The analysis of data was based on two sets of questionnaire, i.e.,the study behaviour questionnaire and the home environment questionnaire. The dependent variable in this study was student achievement in the SRP English examination. From the results of the study and a review of related literature, it is inferred that the independent variables studied had considerable influence on the dependent variable. The study also revealed that the three study behaviour variables and the three home environment variables combined explained 27.6% of the total variance in English achievement; the best single predictor of English achievement was classroom study behaviour; and a substantial amount of variance i n English achievement remained unexplained.The findings have significant long-term implications for English teaching and learning in Malaysian schools. In view of the importance of study behaviours brought to light by this study, it is recommended that good learning strategies be taught to students in schools to facilitate them develop the right attitude towards English learning, and subsequently relevant study behaviour that helps improve their performance in English. It is also suggested that parents need to be kept informed of the objectives and implications of the English programme in schools so that they can provide a supportive environment at home which may help their children do well in English.